Trinity of inflammation, innate immune cells and cross-talk of signalling pathways in tumour microenvironment - Attiq, Ali; Afzal, Sheryar (Frontiers in Pharmacology, 2023)
Unresolved inflammation is a pathological consequence of persistent inflammatory stimulus and perturbation in regulatory mechanisms. It increases the risk of tumour development and orchestrates all stages of tumorigenesis in selected organs. In certain cancers, inflammatory processes create the appropriate conditions for neoplastic transformation. While in other types, oncogenic changes pave the way for an inflammatory microenvironment that leads to tumour development. Of interest, hallmarks of tumour-promoting and cancer-associated inflammation are striking similar, sharing a complex network of stromal (fibroblasts and vascular cells) and inflammatory immune cells that collectively form the tumour microenvironment (TME). The cross-talks of signalling pathways initially developed to support homeostasis, change their role, and promote atypical proliferation, survival, angiogenesis, and subversion of adaptive immunity in TME. These transcriptional and regulatory pathways invariably contribute to cancer-promoting inflammation in chronic inflammatory disorders and foster 'smouldering' inflammation in the microenvironment of various tumour types. Besides identifying common target sites of numerous cancer types, signalling programs and their cross-talks governing immune cells' plasticity and functional diversity can be used to develop new fate-mapping and lineagetracing mechanisms. Here, we review the vital molecular mechanisms and pathways that establish the connection between inflammation and tumour development, progression, and metastasis. We also discussed the cross-talks between signalling pathways and devised strategies focusing on these interaction mechanisms to harness synthetic lethal drug combinations for targeted cancer therapy.